Geometry-Driven Performance of Unit Cells in Multiband Reflective Metasurfaces: A Comparative Study - Taufiqqurrachman; Mohamad Kamal B. A. Rahim; Noor Asmawati Samsuri; Yusuf Nur Wijayanto; Nur Syahirah Mohd Yaziz; Topik Teguh Estu; Sunti Tuntrakool (My University, 2025)
A multiband reflective metasurface can be designed using a multi-ring resonator, where the resonator can take various shapes such as circular, square, hexagonal, triangular, and others. This paper presents a comparative study of unit-cell multiband reflective metasurfaces based on their geometric structure, focusing on reflection magnitude, reflection phase, and bandwidth performance of hexagonal and triangular shapes. Both proposed designs are designed and simulated at X-band frequencies using an F4BMX220 substrate with a thickness of 1.5 mm. Simulation results show that the hexagonal shape offers better reflection performance and a wider bandwidth compared to the triangular shape.
Keywords: Advanced Antenna and Metasurface Technologies; Metamaterials and Metasurfaces Applications; Antenna Design and Analysis